2020
DOI: 10.1186/s12879-020-05447-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Listeria monocytogenes in a patient with meningoencephalitis using next-generation sequencing: a case report

Abstract: Background Listeria monocytogenes (L. monocytogenes) is a facultative intracellular bacterial pathogen which can invade different mammalian cells and reach to the central nervous system (CNS), leading to meningoencephalitis and brain abscesses. In the diagnosis of L. monocytogenes meningoencephalitis (LMM), the traditional test often reports negative owing to the antibiotic treatment or a low number of bacteria in the cerebrospinal fluid. To date, timely diagnosis and accurate treatment remains a challenge for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Prehospital antibiotic use may induce atypical CSF alterations. Monocyte predominance can make the early diagnosis of LMM in patients challenging and occasionally the disease is misdiagnosed as tuberculous meningitis ( 20 ) which is a relatively common disease in northwestern China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prehospital antibiotic use may induce atypical CSF alterations. Monocyte predominance can make the early diagnosis of LMM in patients challenging and occasionally the disease is misdiagnosed as tuberculous meningitis ( 20 ) which is a relatively common disease in northwestern China.…”
Section: Discussionmentioning
confidence: 99%
“…mNGS can detect all nucleic acids in a specimen containing the host and microbial sequences by sequencing the total DNA or RNA to identify pathogens. This approach overcomes the limitations of traditional pathogen detection with expanded coverage and improved sensitivity and is less affected by previous antimicrobial exposure and the length of the course of treatment ( 20 ). The properties support the use of mNGS delivery in rapid diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mNGS is appropriate for various specimen types, including peripheral blood, CSF, tissue, sputum, and bronchoalveolar lavage [ 11 ]. Many reports [ 12 16 ] show the strong potential of mNGS in infectious disease diagnostics compared with traditional methods.…”
Section: Discussionmentioning
confidence: 99%
“…To improve prognosis, early diagnosis is crucial, followed by timely treatment. 41 Early empirical therapy is essential for favorable outcomes of Listeria infection. 42 A retrospective case-control study indicated that delaying appropriate antibiotic therapy for more than 6 hours increased the risk of mortality by 2.78-fold.…”
Section: Discussionmentioning
confidence: 99%